Molecularly imprinted polymers in pharmaceutical sciences. Part I. The principles of molecular imprinting. Applications in drug synthesis and drug delivery systems - Luliński, P. (Polimery, 2010)
This paper is a review of the literature of studies on molecularly imprinted polymers. The studied polymers have found a wide range of applications in medicine and pharmacy due to their ability for selective and multiple adsorption of specific molecules. The fundamentals of the molecular imprinting process (Fig. 1.), and the possibilities of the application of molecularly imprinted polymers in drug synthesis and delivery systems have been presented. The application of molecularly imprinted polymers in pharmaceutical analysis is also discussed in the second part of the paper.